Screening of antioxidant activity and antioxidant compounds of some edible plants of Thailand - Chanwitheesuk A. (2014)
A large number of plants, which have been used as food and herbs in Thailand, were investigated for their antioxidant activity by using a β-carotene bleaching method. The contents of plant chemicals, such as vitamin C, vitamin E, carotenoids, tannin, and total phenolics, were also determined. The results showed that the highest antioxidant activity was found in the plant Gymnema inodorum, followed by Piper sarmentosum and Mentha arvensis, respectively. G. inodorum also contained the highest amount of vitamin E, and M. arvensis contained the highest amount of total xanthophylls. Correlations between the chemical content of each plant and the antioxidant index were observed. The results suggest that chemicals such as vitamin C, vitamin E, carotenoids, and phenolic compounds are the contributors to the antioxidant activity in the plants. © 2004 Elsevier Ltd. All rights reserved.